DNA Origami-Templated Bimetallic Nanostar Assemblies for Ultra-Sensitive Detection of Dopamine - Kaur, Vishaldeep; Sharma, Mridu; Sen, Tapasi (Frontiers in Chemistry, 2021)
The abundance of hotspots tuned via precise arrangement of coupled plasmonic nanostructures highly boost the surface enhanced Raman scattering (SERS) signal enhancements, expanding their potential applicability to a diverse range of applications. Herein, nanoscale assembly of Ag coated Au nanostars in dimer and trimer configurations with tunable nanogap was achieved using programmable DNA origami technique. The resulting assemblies were then utilized for SERS based ultra-sensitive detection of an important neurotransmitter, dopamine. The trimer assemblies were able to detect dopamine with picomolar sensitivity and the assembled dimer structures achieved SERS sensitivity as low as 1 fM with limit of detection of 0.225 fM. Overall, such coupled nanoarchitectures with superior plasmon tunability are promising to explore new avenues in biomedical diagnostic applications.